Disparities in Access to Healthy Diets: How Food Security and Food Shopping Behaviors Relate to Fruit and Vegetable Intake - Drisdelle, Caroline; Kestens, Yan; Hamelin, Anne-Marie; Mercille, Geneviève (Journal of the Academy of Nutrition and Dietetics, 2020)
Food shopping behaviors may help determine how local food environments influence fruit and vegetable (F/V) intake, especially among food insecure households. To examine whether household food security, food access, and food shopping behaviors are associated with F/V intake among residents of a low-income neighborhood. Study design is cross-sectional. A simple random sample of 451 adults from a low-income neighborhood in Montreal (Canada) were recruited through telephone interviews in 2014. Final analyses included 417 participants. Validated assessment tools were applied to measure F/V intake and to distinguish food secure (FS) from food insecure (FI) participants. Neighborhood food access was calculated according to number of food stores within 0.5 miles of road network buffer of participants’ homes. Self-reported food shopping behaviors included trip frequency, store types, and transport used to reach the 3 most frequented stores. Participants also reported on mobility constraints, use of F/V markets, gardening, and perceived access to healthy food. F/V intake was modeled using multivariable linear regression. A sample of adults, of whom 21.3% were living in FI households, reported consuming F/V an average of 4.1 times daily. FI participants had a lower intake of F/V (b = −0.69, P = .04), independent of sociodemographics, food access, resource constraints, perceived access to healthy food, and food shopping behaviors. Participants with mobility constraints had lower F/V intake (b = −0.68, P = .02), while gardening was associated with higher F/V intake (b = 0.59, P = .01). Number of supermarkets (b = −0.06, P = .03) and specialty stores (b = 0.10, P = .04) were associated with F/V intake, although the strength of the association was weak. For FI households, barriers to food access linked to financial challenges are associated with lower intake of F/V. Studies on food environment should include people’s experience of food access to better understand the numerous barriers to F/V consumption faced by FI households.